Documenting hidden apartheid in the Indian diaspora - Mandrika Rupa (Pacific Journalism Review, 2024)
Commentary: This article provides an account of an independent filmmaker’s work in documenting some of the stories from the global Indian diaspora.  Based in Aotearoa New Zealand, with ancestral connections to Fiji, East Africa, UK, US and India, and using documentary making with both its journalistic and artistic purposes, the author firstly refers to the literatures that identifies documentary-making as journalism, diaspora, and the caste system.  She then situates herself within the South Pacific Indian diaspora, before describing her experience in the making of the documentary entitled Hidden Apartheid: A Report on Caste Discrimination. The article concludes by reflecting on her role and the role of documenting hidden discrimination where it exists throughout Indian communities of the diaspora.